LINGUISTIC AND CULTURAL ASPECTS OF HISPANIZATION OF AMERICAN CONTINENT - Korbozerova, Nina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article deals with the research on language contacts on the American continent which remains extremely current today, because in recent years linguists have detailed the object of their studies, specifying it as having introduced such productive approaches as linguosocial, linguocultural, linguocognitive and linguoethnic. Linguistic contacts on the American continent occurred in two significant waves for the life of the continent: the first is the Hispanization of the American Indians in the 15th-16th centuries by the Spanish Conquistadors and the second is the Hispanization of the United States as a result of the emigration, primarily, of Mexicans from the end of the 20th century until today. _____________References:• Zhluktenko, O. (1966). Movni kontakty [Language Contacts]. Vyd-vo Kyivskoho Universytetu.• Zhluktenko, O. (1974). Lingvistychnyi aspekty dvomovnosti: Monohrafiia [Linguistic Aspects of Bilingualism: Monograph]. Vyd-vo Kyivskoho Universytetu.• Kocherhan, M. P. (2008). Zahalne movoznavstvo [General Linguistics]. Akademiia.
Keywords: linguosocial, linguocultural, linguocognitive and linguoethnic approaches, linguistic contacts